AktAR and Akt‐STOPS: Genetically Encodable Molecular Tools to Visualize and Perturb Akt Kinase Activity at Different Subcellular Locations in Living Cells. Issue 5 (9th May 2022) - Zhou, Xin; Mehta, Sohum; Zhang, Jin
Abstract: The serine/threonine protein kinase Akt integrates diverse upstream inputs to regulate cell survival, growth, metabolism, migration, and differentiation. Mounting evidence suggests that Akt activity is differentially regulated depending on its subcellular location, which can include the plasma membrane, endomembrane, and nuclear compartment. This spatial control of Akt activity is critical for achieving signaling specificity and proper physiological functions, and deregulation of compartment‐specific Akt signaling is implicated in various diseases, including cancer and diabetes. Understanding the spatial coordination of the signaling network centered around this key kinase and the underlying regulatory mechanisms requires precise tracking of Akt activity at distinct subcellular compartments within its native biological contexts. To address this challenge, new molecular tools are being developed, enabling us to directly interrogate the spatiotemporal regulation of Akt in living cells. These include, for instance, the newly developed genetically encodable fluorescent‐protein‐based Akt kinase activity reporter (AktAR2), which serves as a substrate surrogate of Akt kinase and translates Akt‐specific phosphorylation into a quantifiable change in Förster resonance energy transfer (FRET). In addition, we developed the Akt substrate tandem occupancy peptide sponge (Akt‐STOPS), which allows biochemical perturbation of subcellular Akt activity. Both molecular tools can be readily targeted to distinct subcellular localizations. Here, we describe a workflow to study Akt kinase activity at different subcellular locations in living cells. We provide a protocol for using genetically targeted AktAR2 and Akt‐STOPS, along with fluorescence imaging in living NIH3T3 cells, to visualize and perturb, respectively, the activity of endogenous Akt kinase at different subcellular compartments. We further describe a protocol for using chemically inducible dimerization (CID) to control the plasma membrane‐specific inhibition of Akt activity in real time. Lastly, we describe a protocol for maintaining NIH3T3 cells in culture, a cell line known to exhibit robust Akt activity. In all, this approach enables interrogation of spatiotemporal regulation and functions of Akt, as well as the intricate signaling networks in which it is embedded, at specific subcellular locations. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Visualizing and perturbing subcellular Akt kinase activity using AktAR and Akt‐STOPS Basic Protocol 2 : Using chemically inducible dimerization (CID) to control inhibition of Akt at the plasma membrane Support Protocol : Maintaining NIH3T3 cells in culture